2020
DOI: 10.1097/mca.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Association of gender with clinical outcomes of patients with acute ST-segment elevation myocardial infarction presenting with acute heart failure

Abstract: Background There is limited data evaluating the sex differences in outcomes of patients with ST-segment elevation myocardial infarction presenting with acute heart failure. We compared the outcomes between women and men with ST-segment elevation myocardial infarction presenting with acute heart failure (Killip classification ≥II). Method All ST-segment elevation myocardial infarction patients presenting to the emergency department of a cardiovascular ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Another five papers reviewed in detail were excluded after due to data from the same cohorts. A total of 15 studies were finally included in the present systematic review and meta-analysis 10–24…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another five papers reviewed in detail were excluded after due to data from the same cohorts. A total of 15 studies were finally included in the present systematic review and meta-analysis 10–24…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 studies were finally included in the present systematic review and meta-analysis. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]…”
Section: Literature Searchmentioning
confidence: 99%
“…Women, especially younger women, have been found to have higher mortality rates from acute myocardial infarction (MI) [14,[105][106][107][108], especially in ST-elevation MI [109]. However, more recent studies show similar mortality outcomes among men and women, both before [110] and after adjusting for risk factors [111][112][113], suggesting that differing CV risk in women may be a driver of perceived mortality differences. Overall CVD mortality in 2016 in women (49.0%) was similar to that in men (51.0%) [1].…”
Section: Outcomes In Women From Racial/ethnic Minority Backgroundsmentioning
confidence: 99%
“…Acute myocardial infarction can lead to sudden death, and continuous myocardial ischemia can eventually develop into heart failure [11]. Studies have shown that early reperfusion therapy is the key to the successful treatment of STEMI.…”
Section: Discussionmentioning
confidence: 99%